Marketing Strategy of Islamic Educational Institutions in Indonesia: Systematic Literature Review - Bayu Pramono; Ahmad Rifauidn; Zainal Muttaqin; Anis Fauzi; Rijal Firdaos (Didaktika: Jurnal Kependidikan, 2025)
This study aims to explore effective marketing strategies to maintain the existence of Islamic Educational Institutions in Indonesia, The method used in this study is a literature review (Systematic literature review) whose data is obtained by reviewing articles on the Google Scholar database site. The results of the study concluded that there are 5 steps of marketing strategy for Islamic educational institutions. First, Determining Customer Value (School Vision and Mission). Second, Determining Segmenting, Targeting, and positioning. Third, Determining the Marketing Mix (Excellence of Educational Products or Services, Competitive Prices, Selection of Strategic School Locations and Comfortable Rooms for Learning, Efficient and Effective Promotion, Competent Human Resources, Complete Infrastructure, Accountable, Friendly, Fast and Quality Educational Service Process). Fourth, direct marketing is achieved by creating a website, optimizing IG, TikTok, and YouTube, installing banners, distributing brochures, and advertising on radio and newspapers. Fifth, Indirect Marketing Through Soft Community Service, Student Achievement, the number of alumni who enter their favorite schools/PTN/Education Abroad, and job matching with companies so that alumni can get job access.